al-Waft ft sharh al-shatibiyyah - Abdul Fattah Al-Qadi (Daralsalam, 2021)
This is the Sharh of the great Egyptian scholar specialist, Abd al-Fattah ibn Abd al-Ghani al-Qadi, as part of the Tahqiq series of works of the Sheikh that Mahad al-Imam al-Shatibi is in the process of publish.